2014
DOI: 10.1371/journal.pone.0111637
|View full text |Cite
|
Sign up to set email alerts
|

miR-27 Negatively Regulates Pluripotency-Associated Genes in Human Embryonal Carcinoma Cells

Abstract: Human embryonic stem cells and human embryonal carcinoma cells have been studied extensively with respect to the transcription factors (OCT4, SOX2 and NANOG), epigenetic modulators and associated signalling pathways that either promote self-renewal or induce differentiation in these cells. The ACTIVIN/NODAL axis (SMAD2/3) of the TGFß signalling pathway coupled with FGF signalling maintains self-renewal in these cells, whilst the BMP (SMAD1,5,8) axis promotes differentiation. Here we show that miR-27, a somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 64 publications
(99 reference statements)
0
10
0
1
Order By: Relevance
“…miR-23 targets TRIM63/MuRF1 and FBXO32/atrogin-1, PTEN, caspase-7, SMAD3, and RAS GTPase-activating protein SH3 domainbinding protein 2 (G3BP2), whereas miR-27 targets FoxO1, SMAD2, SMAD4, and myostatin. 18,20,[34][35][36] We found that miR-23a is lower in diabetic skeletal muscle, compared with controls. The decrease in miR-23a contributes to the welldocumented increase in expression of TRIM63/MuRF1 and FBXO32/atrogin-1 E3 ubiquitin ligases as well as dysfunctional insulin signalling (i.e., increased PTEN and decreased Akt phosphorylation).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…miR-23 targets TRIM63/MuRF1 and FBXO32/atrogin-1, PTEN, caspase-7, SMAD3, and RAS GTPase-activating protein SH3 domainbinding protein 2 (G3BP2), whereas miR-27 targets FoxO1, SMAD2, SMAD4, and myostatin. 18,20,[34][35][36] We found that miR-23a is lower in diabetic skeletal muscle, compared with controls. The decrease in miR-23a contributes to the welldocumented increase in expression of TRIM63/MuRF1 and FBXO32/atrogin-1 E3 ubiquitin ligases as well as dysfunctional insulin signalling (i.e., increased PTEN and decreased Akt phosphorylation).…”
Section: Discussionmentioning
confidence: 56%
“…In our study, delivery of the miR‐23a∼27a∼24‐2 precursor RNA by AAV produces both miR‐23a and miR‐27a, both of which target mRNAs that encode proteins which are relevant to the atrophy and fibrosis processes. miR‐23 targets TRIM63/MuRF1 and FBXO32/atrogin‐1, PTEN, caspase‐7, SMAD3, and RAS GTPase‐activating protein SH3 domain‐binding protein 2 (G3BP2), whereas miR‐27 targets FoxO1, SMAD2, SMAD4, and myostatin . We found that miR‐23a is lower in diabetic skeletal muscle, compared with controls.…”
Section: Discussionmentioning
confidence: 80%
“…Although these cells are considered to be stem-like cancer cells with potentially ambiguous phenotypes, they constitute a robust and simplified means to analyze the differentiation and development during human embryogenesis [ 42 , 43 ]. Because RA-induced NCCIT differentiation has been widely in previous studies [ 44 , 45 ], we selected this carcinoma cell line as a cellular model. A whole transcriptomic analysis and the genome-wide mapping of a transcriptional suppressive markers identified a complex relationship between transcription activation and changes in the epigenetic landscape due to the enzymatic activity of histone demethylases.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, when the Wnt or Notch signaling was downregulated, miR-27 was upregulated or cells were activated by BMP4, CSCs tend to differentiate to non-CSCs ( Fig. 2) [42,43]. All these findings indicated that the heterogeneity of CSCs was the consequences of interaction of intrinsic and extrinsic factors.…”
Section: Sources Of Heterogeneity In Cancer Stem Cellsmentioning
confidence: 97%